Visual servoing by partitioning degrees of freedom. - Oh, P.Y (IEEE Transactions on robotics and automation)
There are many design factors and choices when mounting a vision system for robot control. Such factors may include the kinematic and dynamic characteristics in the robot's degrees of freedom (DOF), which determine what velocities and fields-of-view a camera can achieve. Another factor is that additional motion components (such as pan-tilt units) are often mounted on a robot and introduce synchronization problems. When a task does not require visually servoing every robot DOF, the designer must choose which ones to servo. Questions then arise as to what roles, if any, do the remaining DOF play in the task. Without an analytical framework, the designer resorts to intuition and try-and-see implementations. This paper presents a frequency-based framework that identifies the parameters that factor into tracking. This framework gives design insight which was then used to synthesize a control law that exploits the kinematic and dynamic attributes of each DOF. The resulting multi-input multi-output control law, which we call partitioning, defines an underlying joint coupling to servo camera motions. The net effect is that by employing both visual and kinematic feedback loops, a robot can quickly position and orient a camera in a large assembly workcell. Real-time experiments tracking people and robot hands are presented using a 5-DOF hybrid (3-DOF Cartesian gantry plus 2-DOF pan-tilt unit) robot